Cosmopolitan capitalists : Hong Kong and the Chinese diaspora at the end of the 20th century - Hamilton, Gary G. (University of Washington Press, 1999)
"At midnight on June 30, 1997, Hong Kong became part of the People's Republic of China. The transfer of Hong Kong sovereignty from Great Britain to China was an extraordinary historical event, signifying the end of the West's colonial presence in Asia and the rise of China's hegemony."--Jacket